A method for preparing rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material

By using alkali metal halide flux to perform non-uniform nucleation growth of rare earth alkaline earth manganese-based perovskite oxides under air atmosphere, the problems of energy consumption and material impurity caused by long-term reactions in the prior art are solved, and the preparation of high-purity and high-uniformity materials are achieved, and its application prospects in the fields of thermistors and magnetic sensors are expanded.

CN116903369BActive Publication Date: 2025-03-04UNIV OF SCI & TECH BEIJING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310793390.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-03-04
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The method of synthesizing rare earth alkaline earth manganese-based perovskite oxide materials in the prior art requires high temperature and long-term solid phase reaction, resulting in large energy consumption, complex process and difficult to achieve high purity and uniformity.

Method used

The alkali metal halide is used as flux and non-uniform nucleation trigger to prepare rare earth alkaline earth manganese-based perovskite oxides under an air atmosphere, dissolve the oxide precursor by melting the flux, and achieve non-uniform nucleation growth during the cooling process, reducing the synthesis temperature and time.

Benefits of technology

The preparation of rare earth alkaline earth manganese-based perovskite oxide materials is achieved at a lower reaction temperature and a shorter reaction time, which improves the purity and uniformity of the material, and has application value in the fields of mutation thermistors, magnetic sensors, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903369B_ABST
    Figure CN116903369B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material, which belongs to the field of thermosensitive electronic phase change, and specifically relates to a method for reducing the free energy of new phase formation by using an additive having the dual functions of flux and heterogeneous seed crystal, accelerating the reaction speed, and reducing energy consumption through a two-temperature heat treatment process, which can be used as a method for batch synthesis of rare earth alkaline earth manganese-based perovskite oxide electronic phase change materials. The prepared rare earth alkaline earth manganese-based perovskite oxide electronic phase change material has a crystal structure of ABO3 perovskite structure Re 1‑x Ae x MnO3: Re is a rare earth element, Ae is an alkaline earth metal element, and it has considerable application value in the fields of mutation thermistors, magnetoelectronic devices, thermochromism and infrared camouflage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional materials, sensitive resistor materials and devices, and specifically relates to a technical method for effectively preparing rare earth alkaline earth manganese-based perovskite oxide electronic phase change powders and ceramic materials in an air atmosphere by using alkali metal halides as fluxes and non-uniform nucleation triggers. Background Art

[0002] Among the many strongly correlated oxide semiconductor material systems with metal-insulator phase transition characteristics, rare earth alkaline earth manganese-based perovskite has a wide range of adjustable electronic structure and electrical transport properties [1]. Its chemical formula is Re 1-x Ae x MnO3, where Re is a rare earth element and Ae is an alkaline earth element. The phase change characteristics of rare earth alkaline earth manganese-based perovskite electronic phase change materials can be roughly divided into two categories: the first category is the transition from a low-temperature metal phase to a high-temperature insulator phase, and the representative material is Sm 0.66 Sr 0.34 MnO3, below the phase transition temperature of 85K [2], the material exhibits a metallic phase; when the temperature exceeds the phase transition temperature, the material transforms into an insulator phase, and the resistivity increases by nearly three orders of magnitude. The representative system of the second type of phase transition is Sm 0.25 Ca 0.75 MnO3, near the phase transition temperature of 190K, the electrical transport properties of the material change from a low-temperature insulator phase to a high-temperature metal phase, and the resistivity decreases by 3 orders of magnitude [3]. By changing the types and proportions of rare earth elements and alkaline earth elements, the tolerance factor of the perovskite structure can be adjusted, thereby achieving continuous regulation of the phase transition temperature in a wide range of 100-500K [4-10]. Therefore, this system material has considerable application value in sudden thermistors. In addition, due to the competition and coupling of various interactions between the lattice, charge, orbital and spin degrees of freedom, it has a complex phase diagram and rich physical properties. Among them, the giant magnetoresistance effect, magnetocaloric effect, and metal-insulator transition near the magnetic phase transition point of this material have certain application value in the fields of magnetic heads, magnetic switches, and magnetic sensors

[11] .

[0003] At present, the commonly used method for synthesizing rare earth alkaline earth manganese-based perovskite oxides is the solid phase reaction method, the main process of which is to weigh each raw material according to the stoichiometric ratio and fully grind and mix them, and then perform long-term solid phase reactions at high temperatures of 900℃-1400℃ to achieve material synthesis [12-13]. This method has high energy consumption and is difficult to synthesize pure phase materials. In addition to solid phase reactions, this system material can also be synthesized by the sol-gel method, using high-purity metal nitrates as solutes and citric acid as solvents to prepare precursors and sintering at high temperatures of 1100℃-1300℃ to achieve material synthesis

[14] . However, the cost of the precursors used in this method is relatively high and the process is relatively complicated.

[0004] Since the synthesis temperature of the existing methods for synthesizing rare earth alkaline earth manganese-based perovskite oxide materials is in a relatively high temperature range above 900°C, and multiple solid-phase reactions are usually required to obtain the pure phase material of the system, the process is time-consuming and energy-intensive, which increases the application cost of the system materials. In summary, there is currently a lack of an effective method in the art that can achieve large-scale synthesis of rare earth alkaline earth manganese-based perovskite oxide materials through a single reaction at a relatively low reaction temperature.

[0005] 【1】Dagotto E.Nanoscale Phase Separation and ColossalMagnetoresistance: Springer Berlin Heidelberg,10.1007 / 978-3-662-05244-0[P].2003.

[0006] 【2】Damay F, Nguyen N, Maignan A, et al. Colossal magnetoresistance properties of samarium based manganese perovskites[J]. Solid State Communications, 1996, 98(11):997-1001.

[0007] 【3】Martin C, Maignan A, Hervieu M, et al. Magnetic phase diagrams of L1-xAxMnO3 manganites (L=Pr, Sm; A=Ca, Sr) [J]. Phys.rev.b, 1999.

[0008] 【4】Yang, Wang, Yu, et al. Structure, transport and magnetic properties of electron-doped perovskites RxCa1-xMnO3 (R=La, Y and Ce) [J]. Journal of PhysicsCondensed Matter, 2009.

[0009] 【5】Martin C, Maignan A, Hervieu M, et al. Magnetic phase diagrams of L1-xAxMnO3 manganites (L=Pr, Sm; A=Ca, Sr) [J]. Phys.rev.b, 1999.

[0010] 【6】Hiroyuki,Fujishiro,Tetsuo,et al.Charge Ordering and Sound VelocityAnomaly in La1-XSrXMnO3(X≥0.5)[J].Journal of the Physical Society of Japan,1998,67(8):2582-2585.

[0011] 【7】Kobori H,Hoshino A,Taniguchi T,et al.Two-current spin-dependentconduction in polycrystalline LaMnO3 produced under oxygen gas flow[C] / / AipConference.American Institute of Physics,2013.

[0012] 【8】Nakatsugawa M.Thermoelectric and Magnetic Properties ofPr1xSrxMnO3(0.1x0.7)[J].Materials Transactions,2015,56:864-871.

[0013] 【9】Chmaissem O,Dabrowski B,Kolesnik S,et al.Structural and magneticphase diagrams of La1-xSrxMnO3 and Pr1-ySryMnO3[J].Physical Review B,2003,67(9).

[0014]

[10] Boujelben W,A Cheikh ㏑ Ouhou,Ellouze M,et al.ElectricalProperties in Solid Solution Pr1—xSrxMnO3(0≤x≤0.5)[J].physica statussolidi(a),2015,177(2):503-510.

[0015]

[11] Dabrowski B, Kolesnik S, Baszczuk A, et al. Structural, transport, and magnetic properties of RMnO3 perovskites (R=La, Pr, Nd, Sm, 153Eu, Dy) [J]. JOURNAL OF SOLID STATE CHEMISTRY, 2005.

[0016]

[12] Nakatsugawa M. Thermoelectric and Magnetic Properties of Pr1xSrxMnO3 (0.1 x 0.7) [J]. Materials Transactions, 2015, 56: 864 - 871.

[0017]

[13] Nagaraja B S, Rao A, Babu P D, et al. Structural, electrical, magnetic and thermal properties of Gd1 - xSrxMnO3 (0.2 r x r 0.5) manganites. 2015.

[0018]

[14] Raju K, Sivakumar K V, Reddy P V. Structural, electrical, magnetic, elastic, and internal friction studies of Nd1xCaxMnO3 (x=0.2, 0.33, 0.4, and 0.5) manganites [J]. Journal of Physics & Chemistry of Solids, 2012, 73(3): 430 - 438. Summary of the Invention

[0019] The purpose of the present invention is to provide a method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material; its main concept is: using a molten alkali metal halide flux to fully dissolve the oxide precursor required for the synthesis of the system material, and in the cooling process, based on a certain lattice matching relationship between the rare earth alkaline earth manganese-based perovskite oxide and the gradually precipitated alkali metal halide flux crystals, the rare earth alkaline earth manganese-based perovskite oxide is nucleated and grown on the surface of the flux precipitation crystal in a non-uniform nucleation manner. Compared with the traditional solid-phase reaction method of the system material, the technology provided by the present invention can greatly reduce the material synthesis temperature and reaction time, and improve the purity and uniformity of the prepared material, and can realize the mass preparation of the system material in an air atmosphere, at a lower reaction temperature and a shorter reaction time. In addition, the technology provided by the present invention can realize the growth of the heavy rare earth component rare earth alkaline earth manganese-based perovskite oxide material in a thermodynamically metastable phase under normal conditions in an air atmosphere. By further regulating the composition and proportion of rare earth and alkaline earth elements, a wide range of regulation of the phase change properties and electrical transport relationship of the prepared rare earth alkaline earth manganese-based perovskite oxide metal insulator can be achieved. The prepared materials have application value in the fields of positive and negative resistance temperature coefficient mutation thermistors, magnetoelectronic devices, thermochromism and infrared camouflage.

[0020] A method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material, the method comprising the following steps:

[0021] 1) Design rare earth alkaline earth manganese-based perovskite oxide material components according to the metal-insulator electronic phase transition characteristics to be achieved;

[0022] 2) According to the selected material components, the precursors of rare earth, alkaline earth and manganese elements are weighed and fully mixed according to the stoichiometric ratio of the synthesized rare earth alkaline earth manganese-based perovskite oxide material components, and pre-calcined according to the type of precursor to remove its functional groups irrelevant to the final product; the general formula of the material components is Re 1-x Ae x MnO3, where 0.2≤x

[0023] ≤0.6, the material undergoes a transformation from a low-temperature metal phase to a high-temperature insulator phase under the triggering of the characteristic temperature. By further regulating the types of rare earth and alkaline earth elements, the characteristic temperature triggering the transformation of the material from a low-temperature metal to a high-temperature insulator can be regulated in the range of 20K-497K; and when 0≤x<0.2 and 0.6<x≤1, the material undergoes a transformation from a low-temperature insulator phase to a high-temperature metal phase under the triggering of the characteristic temperature. By further regulating the types of rare earth and alkaline earth elements, the characteristic temperature triggering the phase transformation of the material from a low-temperature insulator to a high-temperature metal can be regulated in the range of 80K-1000K.

[0024] 3) Select an alkali metal halide flux that has a coherent alignment relationship with the intended rare earth alkaline earth manganese-based perovskite oxide on a specific crystal plane according to the crystal structure of the intended rare earth alkaline earth manganese-based perovskite oxide to be prepared. Other halide additives can be further added according to the temperature requirements of the subsequent solid-phase reaction to be used for designing the melting point of the flux. Add the selected flux to the above-mentioned precursor mixed powder in a certain proportion;

[0025] 4) Heat the precursor added with the flux in an air or oxygen atmosphere to a temperature above the melting point of the flux so that the precursor is fully dissolved in the molten flux; then slowly cool it to a temperature below the melting point of the flux, keep it warm for a period of time and then cool it to room temperature. During this process, the rare earth alkaline earth manganese-based perovskite oxide co-precipitates with the gradually solidifying alkali metal halide molten salt through a non-uniform nucleation process.

[0026] 5) Remove the alkali metal halide flux in the obtained powder product by washing with water to obtain the rare earth alkaline earth manganese-based perovskite oxide powder; further add a binder to the obtained powder, cold press it and then sinter it to obtain the rare earth alkaline earth manganese-based perovskite oxide ceramic.

[0027] Further, the chemical composition of the synthesized material, the rare earth alkaline earth manganese-based perovskite oxide, in step 1) is Re 1-x Ae x MnO3, where Re is a rare earth element, including La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, Sc, or a single rare earth element or a combination of multiple rare earth elements; Ae is an alkaline earth metal element, including Mg, Ca, Sr, Ba, which can be doped with a single alkaline earth metal element or mixed with multiple alkaline earth metal elements; the prepared rare earth alkaline earth manganese-based perovskite oxide has the characteristic of metal-insulator phase transition triggered by a characteristic temperature.

[0028] Further, the rare earth elements in step 1) are selected as Sm, Eu, Er, La, and Sm y Eu 1-y , La y Pr 1-y , Er y Tm 1-y , Dy y Ho 1-y (0 < y < 1); Ae is selected as Ca, Sr, Ba, and Ca z Sr 1-z , Ba z , Sr 1-z , Ba z , Ca 1-z (0 < z < 1).

[0029] Furthermore, the rare earth element Re in step 1) can be replaced by trivalent ions with a radius close to that of rare earth ions, including Bi, Sb, In, and Tl.

[0030] Furthermore, the step 2) is to adjust the type and proportion of rare earth and alkaline earth elements to adjust the metal insulator phase transition mode, phase transition trigger temperature, and resistivity mutation degree of the prepared material; the material component is Re 1- x Ae x MnO3, where when 0.2≤x≤0.6, the material undergoes a transition from a low-temperature metal phase to a high-temperature insulator phase under the characteristic temperature trigger, and by further regulating the types of rare earth and alkaline earth elements, the material can be regulated from a low-temperature metal to a high-temperature insulator to trigger a characteristic temperature in the range of 20K-497K; and when 0≤x<0.2 and 0.6<x≤1, the material undergoes a transition from a low-temperature insulator phase to a high-temperature metal phase under the characteristic temperature trigger, and by further regulating the types of rare earth and alkaline earth elements, the material can be regulated from a low-temperature insulator to a high-temperature metal to trigger a characteristic temperature in the range of 80K-1000K. In a preferred embodiment, the component is Dy 0.8 Sr 0.2 The material of MnO3 undergoes a transition from a low-temperature metal phase to a high-temperature insulator phase under the triggering of a characteristic temperature of 20K, and the degree of resistivity mutation triggered by it is 400 times; in another preferred embodiment, the component is La 0.4 Sr 0.6 The material of MnO3 undergoes a transition from a low-temperature metal phase to a high-temperature insulator phase under the triggering of a characteristic temperature of 497K, and the degree of resistivity mutation triggered by it is 200 times; in another preferred embodiment, the component is Sm 0.35 Ca 0.65 The material of MnO3 undergoes a transition from a low-temperature insulator phase to a high-temperature metal phase under the triggering of a characteristic temperature of 80K, and the degree of resistivity mutation triggered by it is 100 times; in another preferred embodiment, the material of PrMnO3 undergoes a transition from a low-temperature insulator phase to a high-temperature metal phase under the triggering of a characteristic temperature of 1000K, and the degree of resistivity mutation triggered by it is 100 times;

[0031] Furthermore, the precursors used in step 2) include oxides, nitrates and carbonates of rare earth, alkaline earth and manganese; rare earth oxide Re2O3, alkaline earth metal carbonate AeCO3 and manganese oxide MnO2 are preferably selected as precursors, and the precursors can be mixed directly or mixed after being pre-calcined and decomposed in air.

[0032] Furthermore, the melting point of the flux described in step 3) is lower than the melting point required for synthesizing alkaline earth-doped rare earth manganese-based perovskite oxides, and it can dissolve the precursor powder in a high-temperature liquid state, so that the precursor powder is evenly dispersed in the flux at high temperature, accelerating the reaction rate; the alkali metal halide flux used has a coherent orientation relationship with the rare earth alkaline earth manganese-based perovskite oxide to be prepared in a certain crystal plane orientation, so when the flux is cooled and precipitated, the non-uniform nucleation of the rare earth alkaline earth perovskite oxide material is triggered. The molar ratio of the cosolvent to the manganese oxide is 0.1-100. In a preferred embodiment, the raw materials used are Sm2O3, SrCO3, MnO2, the flux used is NaCl, and its melting point is 1074K, and the prepared material component is Sm 0.67 Sr 0.33 MnO3, the low temperature metal phase changes to the high temperature insulator phase at the phase transition characteristic temperature of 103K. In another preferred embodiment, the raw materials used are Nd2O3, SrCO3, MnO2, the flux used is KCl, the melting point is 1049K, and the prepared material component is Nd 0.67 Sr 0.33 MnO3, a phase transition from a low-temperature metal phase to a high-temperature insulator phase occurs near the phase transition characteristic temperature of 230K. In another preferred embodiment, the raw materials used are La2O3, SrCO3, and MnO2, and the flux used is LiF, which has a melting point of 1121K. The prepared material components are La 0.8 Sr 0.2 MnO3, at a phase transition characteristic temperature of 398K, undergoes a transition from a low-temperature metal phase to a high-temperature insulator phase, and the resistivity mutation degree triggered by it is 100 times. In another preferred embodiment, the raw materials used are La2O3, CaCO3, and MnO2, the flux used is CsI, with a melting point of 899K, and the synthetic material component is La 0.4 Ca 0.6 MnO3 undergoes a phase transition from a low-temperature insulator phase to a high-temperature metal phase near the phase transition characteristic temperature of 350K, and the resistivity mutation degree triggered by it is 200 times.

[0033] Furthermore, the alkali metal halide flux includes LiF, NaF, KF, RbF, CsF, LiCl, NaCl, KCl, RbCl, CsCl, LiBr, NaBr, KBr, RbBr, CsBr, LiI, NaI, KI, RbI, CsI. A single flux can be used to assist the growth of the new phase, or a mixture of multiple fluxes can be used to assist the growth of the new phase.

[0034] Furthermore, the co-solvent mixture is selected from KCl and RbCl, KCl and NaCl, CsCl and LiBr, KCl and LiCl, and NaCl and LiCl.

[0035] Furthermore, the two-stage heat treatment process of step 4) is as follows: the first stage heat treatment process is selected at a temperature higher than the melting point of the flux used by 1-100°C, preferably 100°C, so that the flux is fully melted and the precursor powder is fully dissolved therein; the second stage heat treatment process temperature is selected at a temperature lower than the melting point of the flux used by 1-100°C, preferably 10°C, so that the rare earth alkaline earth manganese-based perovskite oxide undergoes non-uniform nucleation growth and precipitation on the surface of the flux precipitated due to cooling in a non-uniform nucleation manner; in a preferred example, the raw materials are selected as La2O3, SrCO3, and MnO2, the flux is selected as KCl, the melting point is 776°C, the first stage heat treatment temperature is selected as 776°C, and the second stage heat treatment temperature is selected as 676°C to obtain pure phase La 0.67 Sr 0.33 MnO3; in another preferred embodiment, the raw material is Pr6O 11 , CaCO3, MnO2, the flux is NaCl, whose melting point is 801℃, the first heat treatment temperature is 901℃, and then the second heat treatment is carried out at 800℃ to obtain Pr 0.2 Ca 0.8 MnO3 pure phase powder shows a transition from low-temperature insulator phase to high-temperature metal phase near the phase transition characteristic temperature.

[0036] Furthermore, by adjusting the stoichiometric ratio of rare earth, alkaline earth, manganese element precursors and flux, the temperature of the second stage of the thermal process, the reaction time, and the oxygen partial pressure, the particle size of the prepared rare earth alkaline earth manganese-based perovskite oxide powder can be adjusted; by selecting the type of flux, the surface morphology and surface crystal orientation of the prepared rare earth alkaline earth manganese-based perovskite oxide powder can be adjusted, and further the electronic phase change characteristics can be adjusted; the two-stage heat treatment atmosphere is selected in an air atmosphere, or in an oxygen atmosphere, with an oxygen pressure of 1-500 atmospheres. In a preferred example, the raw materials are selected as Lu2O3, SrCO3, and MnO2, and NaCl and KBr are selected in a ratio of NaCl:KBr=1:2, and heat treatment is performed at 700°C and an oxygen pressure of 500 atmospheres to obtain Lu 0.8 Sr 0.2 MnO3 pure phase powder, the powder particle size is 100nm; in another preferred embodiment, the raw materials are selected as Tm2O3, CaCO3, MnO2, the flux ratio is selected as KCl: LiBr = 1:1, and after being kept at 800℃ for 30 minutes, heat treatment is performed at 750℃ and 1 atmosphere of oxygen pressure to obtain Tm 0.8 Ca 0.2 MnO3 pure phase powder, powder particle size is 10μm.

[0037] The present invention proposes a method for preparing rare earth alkaline earth manganese-based perovskite electronic phase change powder and ceramic material in large quantities. Compared with other methods, the advantage of this method is that by introducing an alkali metal halide flux with a lattice parameter similar to that of the synthetic material, a non-uniform nucleation condition is provided for the growth of the new phase, the free energy of the nucleation growth of the new phase is reduced, and the reaction temperature and reaction time required for material synthesis are greatly reduced, so that the large-scale preparation of high-purity and high-uniformity materials in an air atmosphere can be achieved. By further regulating the rare earth and alkaline earth element components and proportions, the metal-insulator transition temperature of the material can be continuously regulated in a wide range. It has certain application prospects in the fields of sudden thermistors, magnetic sensors, magnetic switches, supercapacitors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The Nd prepared by the flux method proposed in the present invention 0.67 Sr 0.33 From the X-ray diffraction pattern of MnO3 powder, it can be seen that the prepared powder is a pure phase powder.

[0039] Figure 2 The Nd prepared by the flux method proposed in the present invention 0.67 Sr 0.33 The resistivity-temperature curve of MnO3 powder shows that the prepared powder undergoes a transformation from a low-temperature metal phase to a high-temperature insulator phase near the metal-insulator phase transition temperature (230K).

[0040] Figure 3 The Sm prepared by the flux method proposed by the present invention 0.67 Sr 0.33 The resistivity of MnO3 powder material changes with temperature. As the temperature rises, the material undergoes a transition from a low-temperature metal phase to a high-temperature insulator phase at 103K.

[0041] Figure 4 The Sm prepared by the flux method proposed by the present invention 0.15 Ca 0.85 The relationship between the resistivity of MnO3 material and temperature. The material undergoes a phase transition from a low-temperature insulator phase to a high-temperature metal phase around the phase transition temperature of 100K. DETAILED DESCRIPTION

[0042] Unless otherwise specified, the various raw materials used in the present invention can be obtained from the market or prepared according to conventional methods in the art. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of the present invention.

[0043] Other aspects of the present invention will be apparent to those skilled in the art in view of the disclosure herein.

[0044] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0045] Example 1: Weigh Nd2O3, SrCO3, and MnO2 according to the molar ratio of elements Nd: Sr: Mn = 0.67: 0.33: 1, place them in an agate mortar and grind them evenly, then place them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200°C for 8 hours to decompose strontium carbonate. Then weigh KCl at a molar ratio of MnO2: KCl = 1: 2, add it to the powder obtained after pre-sintering, pour it into an agate mortar and grind it evenly, use a press to cold press it into a block with a diameter of 6 mm, then place it in an alumina crucible, first sinter it at 800°C for 30 minutes, then keep it at 750°C for 24 hours, and cool it to room temperature after the reaction is completed. Finally, rinse the powder sample with deionized water and dry it to obtain pure phase Nd 0.67 Sr 0.33 MnO3 powder, a binder is added to the obtained powder, cold pressed and sintered to obtain a ceramic material of this component, which undergoes a phase transition from a low-temperature metal phase to a high-temperature insulator phase near the phase transition characteristic temperature of 230K, and the resistivity mutation degree triggered is 30 times.

[0046] Example 2: Select the raw materials as Sm2O3, SrCO3, and MnO2, weigh them according to the ratio of Sm:Sr:Mn=0.67:0.33:1, put them in an agate mortar, mix them thoroughly, grind them evenly, pour them into an alumina crucible, put them into a muffle furnace, and pre-sinter them at 1200°C for 8 hours to decompose strontium carbonate. Then weigh NaCl according to the molar ratio of MnO2:NaCl=1:2, add it to the powder obtained after pre-sintering, pour it into an agate mortar, grind and mix them thoroughly, use a press to cold-press them into blocks, and then pour them into an alumina crucible. First, sinter them at 840°C for 30 minutes, then slowly cool them to 770°C and keep them warm for 24 hours. After the insulation ends, cool them to room temperature. Grind the sample in a mortar and rinse it with deionized water to obtain a component of Sm 0.67 Sr 0.33 A sample of MnO3 was prepared by adding a binder to the obtained powder and then cold pressing and sintering to obtain a ceramic material of this component. A transition from a low-temperature metal phase to a high-temperature insulator phase occurred near the phase transition characteristic temperature of 103K, and the resistivity mutation degree triggered was 100 times.

[0047] Example 3: Select the raw materials as La2O3, SrCO3, and MnO2. Each raw material is weighed according to the molar ratio of La:Sr:Mn=0.8:0.2:1. After being fully mixed and ground, it is placed in an alumina crucible and placed in a muffle furnace. First, it is kept at 1200℃ for 8 hours to decompose the strontium carbonate. Then, LiF is weighed at a molar ratio of MnO2:LiF=1:2 and added to the powder obtained after pre-sintering. After being fully ground and mixed, it is cold-pressed into blocks using a press. Then, it is poured into an alumina crucible and placed in a muffle furnace. It is kept at 860℃ in the air for 30 minutes, and finally slowly cooled to 820℃ and kept for 24 hours. The blocks are crushed with a mortar to obtain a powder. Finally, the powder is repeatedly rinsed with deionized water and alcohol, and dried. La is obtained. 0.8 Sr 0.2 MnO3 pure phase powder, to which a binder is added, cold pressed and sintered to obtain the ceramic material of this component, a transition from low-temperature metal phase to high-temperature insulator phase occurs near the phase transition characteristic temperature of 398K, and the resistivity mutation degree triggered is 100 times.

[0048] Example 4: Weigh CeO2, SrCO3, and MnO2 according to the molar ratio of Ce: Sr: Mn = 0.4: 0.6: 1, place them in an agate mortar and grind them evenly, then place them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200°C for 8 hours to decompose SrCO3. Then weigh NaF with a molar ratio of MnO2: NaF = 1:2, add it to the powder obtained after pre-sintering, pour it into an agate mortar and grind it evenly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 1000°C in air for 30 minutes, then slowly cool it to 980°C and keep it for 24 hours, use a mortar to crush the blocks to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry it. Pure Ce is obtained. 0.4 Sr 0.6 MnO3 powder, a binder is added to the obtained powder, cold pressed and sintered to obtain a ceramic material of this component, which undergoes a phase transition from a low-temperature metal phase to a high-temperature insulator phase near the phase transition characteristic temperature of 465K, and the resistivity mutation degree triggered is 300 times.

[0049] Example 5: Selecting the raw material as Pr6O 11, MnO2, weigh the raw materials according to the molar ratio of Pr: Mn = 1: 1, grind them evenly, then weigh KF according to the molar ratio of MnO2: KF = 1: 2, pour it into an agate mortar, grind it evenly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 860℃ in air for 30 minutes, then slowly cool it to 820℃ and keep it for 24 hours, grind the blocks with a mortar to get powder, finally rinse the powder repeatedly with deionized water and alcohol, and dry it. Pure phase PrMnO3 powder is obtained, and a binder is added to the obtained powder, cold pressed and sintered to obtain the ceramic material of this component. The transition from low-temperature insulator phase to high-temperature metal phase occurs under the triggering of the characteristic temperature of 1000K, and the degree of resistivity mutation triggered is 100 times.

[0050] Example 6: Weigh Eu2O3, SmCO3, CaCO3, and MnO2 according to the molar ratio of elements Eu: Sm: Ca: Mn = 0.4: 0.5: 0.1: 1, place them in an agate mortar and grind them evenly, then place them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200°C for 8 hours to decompose the calcium carbonate. Then weigh RbF with a molar ratio of MnO2: RbF = 1:2, add it to the powder obtained after pre-sintering, pour it into an agate mortar and grind it evenly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 800°C in air for 30 minutes, then slowly cool it to 750°C and keep it for 24 hours, use a mortar to crush the blocks to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry it. Pure phase Eu is obtained 0.4 Sm 0.5 Ca 0.1 MnO3 powder, a binder is added to the obtained powder, cold pressed and sintered to obtain a ceramic material of this component, which undergoes a transformation from a low-temperature insulator phase to a high-temperature metal phase near the phase transition characteristic temperature of 780K, and the resistivity mutation degree triggered is 50 times.

[0051] Example 7: Weigh the raw materials Gd2O3, SrCO3, BaCO3, and MnO2 according to the ratio of Gd:Sr:Ba:Mn=0.4:0.1:0.5:1, grind them thoroughly and evenly, pour them into an alumina crucible, put them into a muffle furnace, and pre-sinter them at 1200°C for 8 hours to decompose SrCO3 and BaCO3. Then weigh CsF with a molar ratio of MnO2:CsF=1:2, add it to the powder obtained after pre-sintering, pour it into an agate mortar, grind and mix thoroughly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 700°C in air for 30 minutes, then slowly cool it to 680°C and keep it for 24 hours, grind the blocks with a mortar to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry it. The obtained sample is polycrystalline pure phase Gd 0.4 Sr 0.1 Ba 0.5MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature metal phase to a high-temperature insulator phase transition occurs near the phase transition characteristic temperature of 400K, and the resistivity mutation degree triggered is 100 times.

[0052] Example 8: Select the raw materials of Tb4O7, SrCO3, MgCO3, and MnO2, weigh them according to the molar ratio of elements Tb: Sr: Mg: Mn = 0.8: 0.1: 0.1: 1, put them in an agate mortar, mix and grind them evenly, then put them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200°C for 8 hours to decompose strontium carbonate and magnesium carbonate. Then weigh LiCl at a molar ratio of MnO2: LiCl = 1: 2, add it to the powder obtained after pre-sintering, pour it into an agate mortar, grind and mix it evenly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 620°C in air for 30 minutes, then slowly cool it to 600°C and keep it for 24 hours, grind the blocks with a mortar to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry it. The sample obtained is polycrystalline pure phase Tb 0.8 Sr 0.1 Mg 0.1 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature metal phase to a high-temperature insulator phase transition occurs near the phase transition characteristic temperature of 450K, and the resistivity mutation degree triggered is 400 times.

[0053] Example 9: Dy2O3, SrCO3, and MnO2 were weighed according to the molar ratio of Dy: Sr: Mn = 0.8: 0.2: 1, and were placed in an agate mortar and ground evenly, then placed in an alumina crucible, placed in a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose strontium carbonate. Then, NaCl with a molar ratio of MnO2: NaCl = 1: 1 was weighed, added to the powder obtained after pre-fired, poured into an agate mortar, ground and mixed evenly, cold pressed into blocks, then poured into an alumina crucible and placed in a muffle furnace, kept at 820°C in air for 30 minutes, then slowly cooled to 800°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain powder, and the sample obtained by washing and drying was polycrystalline pure phase Dy 0.8 Sr 0.2 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, when triggered by the characteristic temperature of 20K, the transformation from the low-temperature metal phase to the high-temperature insulator phase occurs, and the degree of resistivity mutation triggered is 400 times.

[0054] Example 10: Select the raw materials as Ho2O3, CaCO3, and MnO2, weigh them according to the molar ratio of elements Ho:Ca:Mn=0.2:0.8:1, put them in an agate mortar and grind them evenly, then put them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200℃ for 8 hours to decompose calcium carbonate. Then weigh RbCl with a molar ratio of MnO2:RbCl=1:1, add it to the powder obtained after pre-sintering, pour it into an agate mortar and grind it evenly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 730℃ in 2 atmospheres of oxygen for 30 minutes, then slowly cool it to 700℃ and keep it for 24 hours, crush the blocks with a mortar to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry it to obtain pure phase powder Ho 0.8 Ca 0.2 MnO3, a binder is added to the obtained powder, cold pressed and sintered to obtain a ceramic material of this component, which undergoes a phase transition from a low-temperature insulator phase to a high-temperature metal phase near the phase transition characteristic temperature of 690K.

[0055] Example 11: Er2O3, Tm2O3, SrCO3, and MnO2 were weighed according to the molar ratio of elements Er:Tm:Sr:Mn=0.2:0.2:0.6:1, and were fully mixed and ground and placed in an alumina crucible, placed in a muffle furnace, and pre-calcined at 1200°C for 8 hours to decompose strontium carbonate. Then, CsCl with a molar ratio of MnO2:CsCl=1:3 was weighed, added to the powder obtained after pre-calcination, poured into an agate mortar, fully ground and mixed, cold pressed into blocks, and then poured into an alumina crucible and placed in a muffle furnace, and kept at 680°C for 30 minutes in oxygen at 100 atmospheres of pressure, and then slowly cooled to 620°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain a powder, and finally the powder was repeatedly rinsed with deionized water and alcohol, and dried to obtain pure phase powder Er. 0.2 Tm 0.2 Sr 0.6 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature metal phase to a high-temperature insulator phase transition occurs near the phase transition characteristic temperature of 420K, and the resistivity mutation degree triggered is 300 times.

[0056] Example 12: Select the raw materials Tm2O3, CaCO3, and MnO2, weigh them according to the molar ratio of elements Tm:Ca:Mn=0.8:0.2:1, put them in an agate mortar and grind them evenly, then put them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200°C for 8 hours to decompose the calcium carbonate. Then weigh KCl and LiBr with a molar ratio of MnO2:KCl:LiBr=1:1:1, add them to the powder obtained after pre-sintering, pour them into an agate mortar and grind them evenly, cold press them into blocks, then pour them into an alumina crucible and put them in a muffle furnace, keep them at 800°C in oxygen at 1 atmosphere pressure for 30 minutes, then slowly cool them to 750°C and keep them for 24 hours, grind the blocks with a mortar to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry them. To obtain Tm 0.8 Ca 0.2 MnO3 pure phase powder, add a binder to the obtained powder, cold press and sinter to obtain the ceramic material of this component, the powder particle size is 10μm, and the low-temperature metal phase transforms to the high-temperature insulator phase near the phase transition temperature of 230K, and the resistivity mutation degree triggered is 100 times.

[0057] Example 13: Yb2O3, CaCO3, and MnO2 were weighed in an agate mortar according to the molar ratio of Yb:Ca:Mn=0.85:0.15:1, and were fully ground in an agate mortar, then placed in an alumina crucible, put into a muffle furnace, and pre-calcined at 1200°C for 8 hours to decompose CaCO3. Then, KCl and NaBr with a molar ratio of MnO2:KCl:NaBr=1:2:1 were weighed, added to the powder obtained after pre-calcination, poured into an agate mortar, fully ground and mixed, cold pressed into blocks, then poured into an alumina crucible and put into a muffle furnace, kept at 780°C for 30 minutes in oxygen at 300 atmospheres of pressure, then slowly cooled to 730°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain powder, and finally the powder was repeatedly rinsed with deionized water and alcohol, and dried to obtain pure phase powder Yb 0.85 Ca 0.15 MnO3, add a binder to the obtained powder and then sinter it after cold pressing to obtain the ceramic material of this component. The low-temperature insulator phase transforms to the high-temperature metal phase near the phase transition characteristic temperature of 850K, and the resistivity mutation degree triggered by it is 50 times.

[0058] Example 14: Select the raw materials as Lu2O3, SrCO3, and MnO2, weigh the raw materials according to the molar ratio of Lu:Sr:Mn=0.8:0.2:1, put them in an agate mortar and grind them evenly, then put them in an alumina crucible, put them in a muffle furnace, and pre-burn them at 1200°C for 8 hours to decompose the strontium carbonate. Then weigh NaCl and KBr with a molar ratio of MnO2:NaCl:KBr=1:1:2, add them to the powder obtained after pre-burning, pour them into an agate mortar and grind them evenly, cold press them into blocks, then pour them into an alumina crucible and put them in a muffle furnace, keep them at 750°C in 500 atmospheres of oxygen for 30 minutes, then slowly cool them to 700°C and keep them for 24 hours, grind the blocks with a mortar to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry them. Get Lu 0.8 Sr 0.2 MnO3 pure phase powder with a powder particle size of 100nm is added with a binder to the obtained powder, and then cold pressed and sintered to obtain the ceramic material of this component. The low-temperature metal phase transforms to the high-temperature insulator phase near the phase transition characteristic temperature of 98K, and the resistivity mutation degree triggered is 50 times.

[0059] Example 15: Y2O3, SrCO3, and MnO2 were weighed according to the molar ratio of elements Y: Sr: Mn = 0.4: 0.6: 1, and the mixture was thoroughly mixed and ground, and then placed in an alumina crucible, placed in a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose strontium carbonate. Then, RbBr and LiCl were weighed in a molar ratio of MnO2: RbBr: LiCl = 1: 1.8: 0.2, added to the powder obtained after pre-firing, poured into an agate mortar, thoroughly ground and mixed, cold pressed into blocks, and then poured into an alumina crucible and placed in a muffle furnace, kept at 700°C in air for 30 minutes, then slowly cooled to 650°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain powder, and finally the powder was repeatedly rinsed with deionized water and alcohol, and dried. The obtained sample is polycrystalline pure phase Y 0.4 Sr 0.6 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature metal phase to a high-temperature insulator phase transition occurs near the phase transition characteristic temperature of 130K, and the resistivity mutation degree triggered is 150 times.

[0060] Example 16: Select the raw materials as Sc2O3, CaCO3, and MnO2, weigh them according to the molar ratio of Sc:Ca:Mn=0.4:0.6:1, put them in an agate mortar and grind them evenly, then put them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200°C for 10 hours to decompose CaCO3. Then weigh NaCl and CsBr according to the molar ratio of MnO2:NaCl:CsBr=1:2:2, add them to the powder obtained after pre-sintering, pour them into an agate mortar, grind and mix them evenly, cold press them into blocks, then pour them into an alumina crucible and put them into a muffle furnace, keep them warm at 830°C in air for 30 minutes, then slowly cool them to 750°C and keep them warm for 24 hours, grind the blocks with a mortar to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry them. The obtained sample is polycrystalline pure phase Sc 0.4 Ca 0.6 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature insulator phase transition to a high-temperature metal phase occurs near the phase transition characteristic temperature of 960K, and the resistivity mutation degree triggered is 50 times.

[0061] Example 17: La2O3, SrCO3, and MnO2 were weighed in an agate mortar at a molar ratio of La:Sr:Mn=0.4:0.6:1, and then placed in an alumina crucible and put into a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose SrCO3. Then, LiI and NaI were weighed in a molar ratio of MnO2:LiI:NaI=1:2:1, added to the powder obtained after pre-fired, poured into an agate mortar, and fully ground and mixed, cold pressed into blocks, and then poured into an alumina crucible and put into a muffle furnace, kept at 680°C in air for 30 minutes, then slowly cooled to 600°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain powder, and finally the powder was repeatedly rinsed with deionized water and alcohol, and dried. The obtained sample is polycrystalline pure phase La 0.4 Sr 0.6 MnO3, add a binder to the obtained powder, cold press and sinter to obtain the ceramic material of this component, which undergoes a transition from a low-temperature metal phase to a high-temperature insulator phase under the triggering of the characteristic temperature of 497K, and the degree of resistivity mutation triggered is 200 times

[0062] Example 18: La2O3, CaCO3, and MnO2 are weighed according to the molar ratio of La:Ca:Mn=0.4:0.6:1, and are placed in an agate mortar to be fully ground and evenly mixed. Then, they are placed in an alumina crucible and placed in a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose CaCO3. Then, CsI with a molar ratio of MnO2:CsI=1:1 is weighed, added to the powder obtained after pre-fired, poured into an agate mortar to be fully ground and mixed evenly, cold-pressed into blocks, and then poured into an alumina crucible and placed in a muffle furnace, kept at 700°C in air for 30 minutes, then slowly cooled to 630°C and kept for 24 hours, and the blocks are crushed in a mortar to obtain a powder. Finally, the powder is repeatedly rinsed with deionized water and alcohol, and dried. The synthetic material component is La 0.4 Ca 0.6 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature insulator phase transition to a high-temperature metal phase occurs near the phase transition characteristic temperature of 350K, and the resistivity mutation degree triggered is 200 times.

[0063] Example 19: Sm2O3, CaCO3, and MnO2 were weighed in an agate mortar according to the molar ratio of elements Sm:Ca:Mn=0.35:0.65:1, and were placed in an agate mortar and ground evenly, then placed in an alumina crucible, placed in a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose CaCO3. Then, KI and RbI with a molar ratio of MnO2:KI:RbI=1:2:1 were weighed, added to the powder obtained after pre-firing, poured into an agate mortar, ground and mixed evenly, cold pressed into blocks, then poured into an alumina crucible and placed in a muffle furnace, kept at 700°C in air for 30 minutes, then slowly cooled to 630°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain powder, and finally the powder was repeatedly rinsed with deionized water and alcohol, and dried. The obtained sample is polycrystalline pure phase Sm 0.35 Ca 0.65 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, when triggered by the characteristic temperature of 80K, the transformation from the low-temperature insulator phase to the high-temperature metal phase occurs, and the degree of resistivity mutation triggered is 100 times.

[0064] Example 20: Bi2O3, CaCO3, SrCO3, and MnO2 are weighed according to the molar ratio of the elements Bi:Ca:Sr:Mn=0.4:0.3:0.3:1, and are placed in an agate mortar and ground evenly. Then, they are placed in an alumina crucible and placed in a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose SrCO3 and CaCO3. Then, CsI with a molar ratio of MnO2:CsI=1:2 is weighed, added to the powder obtained after pre-firing, poured into an agate mortar, ground and mixed evenly, cold-pressed into blocks, and then poured into an alumina crucible and placed in a muffle furnace. They are kept at 650°C in air for 30 minutes, then slowly cooled to 600°C and kept for 24 hours, and the blocks are crushed in a mortar to obtain a powder. Finally, the powder is repeatedly rinsed with deionized water and alcohol, and dried. The obtained sample is polycrystalline pure phase Bi 0.4 Ca 0.3 Sr 0.3 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature insulator phase transition to a high-temperature metal phase occurs near the phase transition characteristic temperature of 530K, and the resistivity mutation degree triggered is 200 times.

[0065] Example 21: Dy2O3, Ho2O3, SrCO3, and MnO2 were weighed according to the molar ratio of the elements Dy:Ho:Sr:Mn=0.1:0.1:0.8:1, and were placed in an agate mortar and ground evenly, then placed in an alumina crucible, placed in a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose the strontium carbonate. Then, RbF with a molar ratio of MnO2:RbF=1:2 was weighed, added to the powder obtained after pre-firing, poured into an agate mortar, ground and mixed evenly, cold pressed into blocks, then poured into an alumina crucible and placed in a muffle furnace, kept at 800°C in air for 30 minutes, then slowly cooled to 750°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain a powder, and finally the powder was repeatedly rinsed with deionized water and alcohol, and dried. The obtained sample is a polycrystalline pure phase Dy 0.1 Ho 0.1 Sr 0.8 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature metal phase to a high-temperature insulator phase transition occurs near the phase transition characteristic temperature of 120K, and the resistivity mutation degree triggered is 200 times.

[0066] Example 22: Select the raw materials of Sb2O3, BaCO3, SrCO3, and MnO2, and weigh them according to the molar ratio of elements Sb:Ba:Sr:Mn=0.05:0.15:0.8:1, put them in an agate mortar and grind them evenly, then put them in an alumina crucible, put them in a muffle furnace, and pre-sinter them at 1200℃ for 8 hours to decompose strontium carbonate and barium carbonate. Then weigh RbF with a molar ratio of MnO2:RbF=1:2, add it to the powder obtained after pre-sintering, pour it into an agate mortar, grind and mix it evenly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 800℃ in air for 30 minutes, then slowly cool it to 750℃ and keep it for 24 hours, grind the blocks with a mortar to obtain powder, rinse the powder, and dry it. To obtain polycrystalline pure phase powder Sb 0.05 Ba 0.15 Sr 0.8 MnO3, add a binder to the obtained powder and sinter it after cold pressing to obtain the ceramic material of this component. The low-temperature metal phase transforms to the high-temperature insulator phase near the phase transition characteristic temperature of 140K, and the resistivity mutation degree triggered is 300 times.

[0067] Example 23: In2O3, BaCO3, CaCO3, and MnO2 are weighed according to the molar ratio of the elements In:Ba:Ca:Mn=0.4:0.3:0.3:1, and are placed in an alumina crucible after being fully ground and evenly mixed. The mixture is then placed in a muffle furnace and pre-fired at 1200°C for 8 hours to decompose calcium carbonate and barium carbonate. RbF is then weighed in a molar ratio of MnO2:RbF=1:2, and added to the powder obtained after pre-firing. The mixture is poured into an agate mortar, fully ground and mixed, and cold pressed into blocks. The mixture is then poured into an alumina crucible and placed in a muffle furnace. The mixture is kept at 800°C in air for 30 minutes, and then slowly cooled to 750°C and kept for 24 hours. The blocks are crushed in a mortar to obtain a powder. Finally, the powder is repeatedly rinsed with deionized water and alcohol, and dried. Polycrystalline pure phase powder In is obtained. 0.4 Ba 0.3 Ca 0.3 MnO3, add a binder to the obtained powder and sinter it after cold pressing to obtain the ceramic material of this component. The low-temperature metal phase transforms to the high-temperature insulator phase near the phase transition characteristic temperature of 760K, and the resistivity mutation degree triggered is 100 times.

[0068] Example 24: Select the raw materials of Tl2O3, CaCO3, SrCO3, and MnO2, and weigh them according to the molar ratio of elements Tl:Ca:Sr:Mn=0.15:0.4:0.45:1, put them in an agate mortar and grind them evenly, then put them in an alumina crucible, and pre-sinter them at 1200℃ in a muffle furnace for 8 hours to decompose CaCO3 and SrCO3. Then weigh KF with a molar ratio of MnO2:KF=1:2, add it to the powder obtained after pre-sintering, pour it into an agate mortar and grind it evenly, cold press it into blocks, then pour it into an alumina crucible and put it into a muffle furnace, keep it at 860℃ in air for 30 minutes, then slowly cool it to 820℃ and keep it for 24 hours, grind the blocks with a mortar to obtain powder, and finally rinse the powder repeatedly with deionized water and alcohol, and dry it. The pure phase powder Tl is obtained. 0.15 Ca 0.4 Sr 0.45 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature insulator phase transition to a high-temperature metal phase occurs near the phase transition characteristic temperature of 560K, and the resistivity mutation degree triggered is 200 times.

[0069] Example 25: La2O3, SrCO3, and MnO2 are weighed according to the molar ratio of La:Sr:Mn=0.67:0.33:1, and are placed in an agate mortar and ground evenly. Then, they are placed in an alumina crucible and placed in a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose the strontium carbonate. Then, KCl with a molar ratio of MnO2:KCl=1:2 is weighed, added to the powder obtained after pre-firing, poured into an agate mortar, ground and mixed evenly, cold-pressed into blocks, and then poured into an alumina crucible and placed in a muffle furnace. They are kept at 776°C in the air for 30 minutes, then slowly cooled to 676°C and kept warm for 24 hours. The blocks are crushed in a mortar to obtain a powder, and finally the powder is repeatedly rinsed with deionized water and alcohol, and dried. Pure phase powder La is obtained. 0.67 Sr 0.33 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature metal phase transition to a high-temperature insulator phase occurs around 400K, and the resistivity mutation degree triggered is 200 times.

[0070] Example 26: Pr6O was weighed according to the ratio of Pr:Ca:Mn = 0.2:0.8:1 11,CaCO3,MnO2,are fully ground in an agate mortar and placed in an alumina crucible. They are kept in a muffle furnace at 1200℃ for 8 hours to decompose CaCO3. Then, NaCl with a molar ratio of MnO2:NaCl=1:1 is weighed and added to the powder obtained after pre-sintering. The mixture is fully ground and mixed in an agate mortar, cold pressed into blocks, and then poured into an alumina crucible and placed in a muffle furnace. The mixture is kept in air at 901℃ for 30 minutes, then slowly cooled to 800℃ and kept in a muffle furnace for 24 hours. The blocks are crushed in a mortar to obtain powder. Finally, the powder is repeatedly rinsed with deionized water and alcohol and dried. Pure phase powder Pr is obtained. 0.2 Ca 0.8 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, undergoes a phase transition from low-temperature insulator to high-temperature metal at around 265K, and the resistivity mutation degree triggered is 100 times.

[0071] Example 27: La2O3, PrCO3, SrCO3, and MnO2 were weighed according to the molar ratio of La:Pr:Sr:Mn=0.4:0.3:0.3:1, and they were placed in an agate mortar and ground evenly, then placed in an alumina crucible, put into a muffle furnace, and pre-fired at 1200°C for 8 hours to decompose SrCO3. Then, CsI with a molar ratio of MnO2:CsI=1:2 was weighed, added to the powder obtained after pre-firing, poured into an agate mortar, ground and mixed evenly, cold pressed into blocks, then poured into an alumina crucible and placed in a muffle furnace, kept at 650°C in air for 30 minutes, then slowly cooled to 600°C and kept for 24 hours, and the blocks were crushed with a mortar to obtain powder, and finally the powder was repeatedly rinsed with deionized water and alcohol, and dried. The obtained sample is polycrystalline pure phase La 0.4 Pr 0.3 Sr 0.3 MnO3, adding a binder to the obtained powder and cold pressing and sintering to obtain the ceramic material of this component, a low-temperature metal phase to a high-temperature insulator phase transition occurs near the phase transition characteristic temperature of 380K, and the resistivity mutation degree triggered is 100 times.

[0072] Example 28: Select the raw materials as Sm2O3, CaCO3, and MnO2. Each raw material is weighed according to the molar ratio of Sm:Ca:Mn=0.15:0.85:1. After being fully mixed and ground, it is placed in an alumina crucible and placed in a muffle furnace. First, it is kept at 1200℃ for 8 hours to decompose the calcium carbonate. Then, LiF is weighed at a molar ratio of MnO2:LiF=1:2 and added to the powder obtained after pre-sintering. After being fully ground and mixed, it is cold-pressed into blocks using a press. Then, it is poured into an alumina crucible and placed in a muffle furnace. It is kept at 860℃ in the air for 30 minutes, and finally slowly cooled to 820℃ and kept for 24 hours. The blocks are crushed with a mortar to obtain a powder. Finally, the powder is repeatedly rinsed with deionized water and alcohol, and dried. Sm 0.15 Ca 0.85 MnO3 pure phase powder, to which a binder is added, cold pressed and sintered to obtain a ceramic material of this component, a transition from a low-temperature metal phase to a high-temperature insulator phase occurs near the phase transition characteristic temperature of 100K, and the resistivity mutation degree triggered is 100 times.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of the substantial technical content of the present invention. The substantial technical content of the present invention is broadly defined in the scope of the claims of the application. Any technical entity or method completed by others, if it is exactly the same as that defined in the scope of the claims of the application or an equivalent variation, will be deemed to be included in the scope of the claims.

Claims

1. A method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material, characterized in that: The following steps are involved: 1) Design rare earth alkaline earth manganese-based perovskite oxide material components according to the metal-insulator electronic phase transition characteristics to be achieved; 2) According to the selected material components, the precursors of rare earth, alkaline earth and manganese elements are weighed and fully mixed according to the stoichiometric ratio of the synthesized rare earth alkaline earth manganese-based perovskite oxide material components to obtain a precursor, and pre-calcined according to the type of the precursor to remove its functional groups irrelevant to the final product; the general formula of the material components is Re 1-x Ae x MnO3, wherein when 0.2≤x≤0.6, the material undergoes a transformation from a low-temperature metal phase to a high-temperature insulator phase under the triggering of a characteristic temperature, and the material is triggered from a low-temperature metal to a high-temperature insulator by regulating the types of rare earth and alkaline earth elements to achieve the control of the characteristic temperature in the range of 20K-497K; and when 0≤x<0.2 and 0.6<x≤1, the material undergoes a transformation from a low-temperature insulator phase to a high-temperature metal phase under the triggering of a characteristic temperature, and the material is triggered from a low-temperature insulator to a high-temperature metal by regulating the types of rare earth and alkaline earth elements to achieve the control of the characteristic temperature in the range of 80K-1000K; 3) According to the crystal structure of the rare earth alkaline earth manganese-based perovskite oxide to be prepared, an alkali metal halide flux having a coherent paraposition relationship with the rare earth alkaline earth manganese-based perovskite oxide on a specific crystal plane is selected, and other halide additives are added according to the temperature requirements of the subsequent solid phase reaction to be used, and the melting point of the flux is designed; the selected flux is added to the above-mentioned precursor, and the mixture is fully ground and mixed; 4) A two-stage heat treatment process is adopted. First, the precursor with the flux added is cold pressed into a block by a press. The first stage of the heat treatment process is to heat it to above the melting point of the flux in an air or oxygen atmosphere so that the precursor is fully dissolved in the molten flux. The second stage of the heat treatment process is to slowly cool it to below the melting point of the flux, keep it warm for a period of time, and then cool it to room temperature. During this process, rare earth alkaline earth manganese-based perovskite oxides are precipitated together with the gradually solidified alkali metal halide molten salt in a non-uniform nucleation process; 5) removing the alkali metal halide flux in the obtained powder product by water washing, thereby obtaining rare earth alkaline earth manganese-based perovskite oxide powder; adding a binder to the obtained powder, cold pressing and then sintering to obtain rare earth alkaline earth manganese-based perovskite oxide ceramics; Step 3) the alkali metal halide flux comprises one or more of LiF, NaF, KF, RbF, CsF, LiCl, NaCl, KCl, RbCl, CsCl, LiBr, NaBr, KBr, RbBr, CsBr, LiI, NaI, KI, RbI, CsI; The two-stage heat treatment process of step 4) is as follows: the temperature of the first stage heat treatment process is selected to be 1-100°C higher than the melting point of the flux used; the temperature of the second stage heat treatment process is selected to be 1-100°C lower than the melting point of the flux used; by adjusting the stoichiometric ratio of the rare earth, alkaline earth, manganese element precursors and the flux, the temperature of the second stage heat treatment process, the reaction time, and the oxygen partial pressure, the particle size of the prepared rare earth alkaline earth manganese-based perovskite oxide powder can be adjusted; The surface morphology and surface crystal orientation of the prepared rare earth alkaline earth manganese-based perovskite oxide powder are regulated by selecting the type of flux, thereby achieving regulation of its electronic phase change characteristics; the oxygen pressure of the air or oxygen atmosphere is 1-500 atmospheres.

2. The method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material according to claim 1, characterized in that: The chemical composition of the synthesized material rare earth alkaline earth manganese-based perovskite oxide in step 1) is Re 1-x Ae x MnO3, where Re Rare earth elements include one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc; Ae Alkaline earth elements include one or more of Mg, Ca, Sr and Ba.

3. The method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material as claimed in claim 2, characterized in that: Step 1) The rare earth elements selected are Sm, Eu, Er, La, Sm y Eu 1-y , La y Pr 1-y , Er y Tm 1-y , Dy y Ho 1-y , where the value range of y is 0 < y < 1; Ae is selected from Ca, Sr, Ba, Ca z Sr 1-z , Ba z Sr 1-z , Ba z Ca 1-z , where the value range of z is 0 < z < 1.

4. The method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material as claimed in claim 2, characterized in that: Step 1) The rare earth element Re Replace with trivalent ions with a radius close to that of rare earth ions, including Bi, Sb, In, and Tl.

5. The method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material according to claim 1, characterized in that: The precursors used in step 2) include rare earth oxides, rare earth nitrates, rare earth carbonates, alkaline earth oxides, alkaline earth nitrates, alkaline earth carbonates, manganese oxides, manganese nitrates, and manganese carbonates.

6. The method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material according to claim 1, characterized in that: Step 2) Select rare earth oxides Re 2O3, alkaline earth carbonate Ae CO3 and manganese oxide MnO2 are precursors, and the precursors are directly mixed or mixed after being pre-calcined and decomposed in air.

7. The method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material according to claim 1, characterized in that: Step 3) The molar ratio of the flux to the oxide of the manganese element is 0.1-100.

8. The method for preparing a rare earth alkaline earth manganese-based perovskite electronic phase change ceramic material according to claim 1, characterized in that: The flux mixture is selected from a mixture of KCl and RbCl, a mixture of KCl and NaCl, a mixture of CsCl and LiBr, a mixture of KCl and LiCl, and a mixture of NaCl and LiCl.

Citation Information

Patent Citations

  • Synthesis method of metastable-state rare-earth nickel-based perovskite oxide powder material

    CN109503165A